Mechanical Performance of Volcanic Ash Concrete Showing Modulus Reduction with Strength Retention - Pinto-Almeida, Carlos; Abril-Camino, Andrés; Abril-Camino, Daniel (Salehan Institute of Higher Education, 2025)
This study aims to evaluate the mechanical behavior of concrete that incorporates 51.3% raw volcanic ash into its structure, focusing on its static elasticity modulus and compressive strength. Cylindrical concrete samples were prepared via the mix design commonly used in practice in Baños, Tungurahua, Ecuador. Three curing methods were applied: immersion, water spraying, and no curing. Compressive strength tests were conducted at 3, 7, 14, 21, and 28 days, whereas the static modulus was measured at 28 days following ASTM C469. Despite the high use of ash in the mixture, the mixtures achieved adequate compressive strengths for structural applications, reaching 28.05 MPa. However, a significant reduction in the static modulus was observed, with experimental values of approximately 7.06 GPa, whereas the value of 24.89 GPa was predicted by the equations given in ACI318. The use of raw volcanic ash in structural mixes requires modifications to deformation and stiffness calculations to ensure seismic performance, suggesting the need to review local regulations on traditional mixes. Based on the experimental data, an alternative empirical model, the VAM model, was proposed to better predict the elastic modulus of concrete with high volcanic ash content. The findings reveal a dual function of ash, acting as a pozzolanic material and as a low-density aggregate, highlighting the need to adjust the design equations when raw volcanic ash is used. This work contributes to the sustainable design of concrete mixtures in seismic regions.